(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The novel coronavirus caused by COVID-19 is a global pandemic that has affected the world in an unexpected way. The pandemic has impacted economic activity in the whole world through lockdowns directly and indirectly. It has affected global trade and growth. This article explores the impact of COVID-19 on the inflation and unemployment and looks at the Indian scenario amid the COVID-19 crisis. Since this is a current issue, newspapers, Government reports as well as research by leading banks are the basis for this article. The slowdown raised in the economy due to the pandemic requires efficient and extreme measures to curb the losses. Continuous Rising inflation can be said a direct cause of the pandemic. The current situation demands measures to control it.